(untitled) (Journal of Partial Differential Equations, 1991)
In this paper the extinction properties of solutions to both linear and nonlinear hyperbolic equations, which reflect the effect of damping boundary conditions and have not been explicitly stated in literature before, are introduced and extensively studied.